2010
DOI: 10.4103/0971-4065.73442
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic exercise and resistance training on lipid profiles and inflammation status in patients on maintenance hemodialysis

Abstract: Physical function limitation is a common disorder in chronic hemodialysis (HD) patients, relating to increased morbidity and mortality. The aim of this study was to determine the effects of aerobic and resistance trainings on blood lipids and inflammation status in HD patients. Out of 30 volunteer males who had been undergoing conventional maintenance HD within an HD unit in Tehran, 21 subjects were enrolled. They were randomly assigned into aerobic exercise group – resistance training group undergoing an 8-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 34 publications
(40 reference statements)
0
40
0
Order By: Relevance
“…The impact of IDE on Kt/V is inconsistent in the literature, with both positive (Kong et al 1999;Parsons et al 2006) and no changes reported (Afshar et al 2010;Kirkman et al 2013). Compared with the control session, Kt/V was found to be slightly, but significantly greater during the 55% protocol, but not during the 70% protocol.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The impact of IDE on Kt/V is inconsistent in the literature, with both positive (Kong et al 1999;Parsons et al 2006) and no changes reported (Afshar et al 2010;Kirkman et al 2013). Compared with the control session, Kt/V was found to be slightly, but significantly greater during the 55% protocol, but not during the 70% protocol.…”
Section: Discussionmentioning
confidence: 70%
“…Intradialytic exercise (IDE) as a therapy for HD patients is utilized in few North American dialysis programs. Benefits of IDE for patients include improvements in aerobic capacity (V O 2peak ) (Ouzouni et al 2009), leg muscle strength (Chen et al 2010), quality of life (Ouzouni et al 2009), as well as lower markers of inflammation (Afshar et al 2010) and hospital usage (Parker et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…From 1,706 potential studies, 24 RCTs [3,4,5,6,7,8,9,10,11,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32] fulfilled the inclusion criteria. Kouidi et al published two duplicated studies in different magazines [3,17].…”
Section: Resultsmentioning
confidence: 99%
“…Kouidi et al published two duplicated studies in different magazines [3,17]. Two studies conducted both aerobic exercise and resistance exercise training; the data were extracted separately [7,20]. A flow diagram of search and selection is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation